Corporate Governance and Humble Leadership as Antecedents of Corporate Financial Performance: Monetary Incentive as a Moderator - Zahoor, Sajjad; Yang, Shuili; Ren, Xiaoyan; Haider, Syed Arslan (Frontiers in Psychology, 2022)
Investors' confidence in the financial market is boosted by good corporate governance. Good governance generates trust and improves an organizations financial performance. But organizations with bad management lose the trust of their stakeholders because they don't do well financially. Therefore, the purpose of this study is to examine influence of corporate governance on financial performance through mediating the role of humble leadership and monetary incentive as a moderator between corporate governance and humble leadership. Data were collected from 300 respondents that were working on various cement manufacturing organizations located in different cities of Pakistan. The analysis performs using SPSS software version 25 and AMOS version 22 software was used to work out the study size of the sample. The result revealed that framework of corporate governance positively impacts in terms of financial performance. Furthermore, humble leadership positively and significantly mediates corporate governance and financial performance is inextricably linked. However, the monetary incentive acts as a moderator between corporate governance and humble leadership, but despite of strengthening, it is weakening corporate governance’s impact on humble leadership. This study contributes towards literature, specifically towards expectancy theory literature. Finally, some theoretical and practical implications on an organizational level are offered, describing how corporate governance influences the financial performance within the organization, and research limitations and future directions are presented.